Choosing to teach : motivating factors in Finnish students' decisions to teach - Balch-Crystal, Elizabeth (2023)
The quality of an education system hinges on the quality of its teacher workforce. Teacher quality, in turn, is partially determined by who chooses to become a teacher. Finland, with its renowned teacher workforce, provides an interesting context within which to investigate individuals’ motivations for becoming a teacher. Thus, the present study seeks to investigate the question: What factors motivate the decisions of Finnish students to become teachers? To investigate this question, a survey was administered to first-year primary school (class) teacher education students during an orientation session at a medium-sized university in Finland. Summary statistics were calculated for the demographic, Likert scale, and ranking questions, and directed, or theory-driven, content analysis was used to analyze the open-ended survey questions. Altruistic motivations, including a desire to help society and a desire to work with children, were the most influential factors impacting participants’ decisions to teach, followed by intrinsic motivations, such as a passion for pedagogy. Extrinsic motivations, social influences, and Finland-specific factors were generally less influential, but still played a role in participants’ decisions. The results both support and expand upon existing theories of teacher motivation and signal a need for further qualitative investigations into the motivations of Finnish students for becoming teachers. Some observed motivations, including prior teaching experiences and a belief that one possesses a natural talent for teaching, could also be leveraged in the development of teacher recruitment programs in countries struggling to attract teachers to the profession.